2021
DOI: 10.3389/fpsyg.2021.718440
|View full text |Cite
|
Sign up to set email alerts
|

The Hierarchy of Defense Mechanisms: Assessing Defensive Functioning With the Defense Mechanisms Rating Scales Q-Sort

Abstract: The psychodynamic concept of defense mechanisms is nowadays considered by professionals with various theoretical orientations of great importance in the understanding of human development and psychological functioning. More than half century of empirical research has demonstrated the impact of defensive functioning in psychological well-being, personality organization and treatment process-outcome. Despite the availability of a large number of measures for their evaluation, only a few instruments assess the wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 42 publications
1
47
0
1
Order By: Relevance
“…Adaptive defenses, such as altruism, humour, and sublimation, are in maintaining physical and mental health across the lifespan (Beresford, 2012 ; Conversano, 2021 ; Malone et al ., 2013 ; Metzger, 2014 ). Conversely, over-reliance on immature defenses, such as projective identification and splitting, is associated with greater symptom severity (Boldrini et al ., 2020 ; Prout et al ., 2020), suicide risk (Hovanesian et al ., 2009 ), personality disorders (Lingiardi & Giovanardi, 2017 ; Maffei et al ., 1995 ; Kempe et al ., 2021 ), insecure attachment (Békés et al ., 2021a ; Tanzilli et al ., 2021), negative physical health outcomes (Di Giuseppe et al ., 2018 ) and high level of stress (Aafjes-Van Doorn et al ., 2021 ; Di Giuseppe et al ., 2021 a).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Adaptive defenses, such as altruism, humour, and sublimation, are in maintaining physical and mental health across the lifespan (Beresford, 2012 ; Conversano, 2021 ; Malone et al ., 2013 ; Metzger, 2014 ). Conversely, over-reliance on immature defenses, such as projective identification and splitting, is associated with greater symptom severity (Boldrini et al ., 2020 ; Prout et al ., 2020), suicide risk (Hovanesian et al ., 2009 ), personality disorders (Lingiardi & Giovanardi, 2017 ; Maffei et al ., 1995 ; Kempe et al ., 2021 ), insecure attachment (Békés et al ., 2021a ; Tanzilli et al ., 2021), negative physical health outcomes (Di Giuseppe et al ., 2018 ) and high level of stress (Aafjes-Van Doorn et al ., 2021 ; Di Giuseppe et al ., 2021 a).…”
Section: Introductionmentioning
confidence: 98%
“…Among the most popular, the Defense Mechanisms Manual is used to rate three defense mechanisms - denial, projection, and identification - as revealed in stories told to TAT and CAT cards (Cramer, 1991 ). This measure has demonstrated validity and reliability (Hibbard & Porcerelli, 1998 ; Porcerelli et al ., 2010 ), however it provides limited information due to the small number of defenses assessed (Nimroody et al ., 2019 ; Di Giuseppe et al ., 2021 b). Another method is the comprehensive assessment of defense style (CADS) (Laor et al ., 2001 ), a 72-item questionnaire for assessing 28 defenses organized into three factors - other-oriented, self-oriented, and mature.…”
Section: Introductionmentioning
confidence: 98%
“…Defense mechanisms higher in the hierarchy (i.e., high adaptive defenses) do not follow the differential criteria described in Cramer's theory (Beresford, 2012). More than 30 years research with the Defense Mechanisms Rating Scales (DMRS; Perry, 1990) and its derivative measures (DMRS-Q; Di Giuseppe et al, 2014;Di Giuseppe and Perry, 2021;DMRS-SR-30;Di Giuseppe et al, 2020a) have demonstrated that individuals using mature defenses can: (1) be partially or fully aware of their activation (e.g., altruism, self-assertion, or self-observation); (2) intentionally use an adaptive defensive strategy to deal with internal conflict or stressful situations (e.g., anticipation or suppression); and…”
mentioning
confidence: 99%
“…Defense mechanisms higher in the hierarchy (i.e., high adaptive defenses) do not follow the differential criteria described in Cramer's theory (Beresford, 2012 ). More than 30 years research with the Defense Mechanisms Rating Scales (DMRS; Perry, 1990 ) and its derivative measures (DMRS-Q; Di Giuseppe et al, 2014 ; Di Giuseppe and Perry, 2021 ; DMRS-SR-30; Di Giuseppe et al, 2020a ) have demonstrated that individuals using mature defenses can: (1) be partially or fully aware of their activation (e.g., altruism, self-assertion, or self-observation); (2) intentionally use an adaptive defensive strategy to deal with internal conflict or stressful situations (e.g., anticipation or suppression); and (3) increase the probability of a gratifying resolution of the internal or external stressors without reality distortion (e.g., self-assertion or sublimation). In light of these findings, we affirm that the hierarchy of defense mechanisms (Vaillant, 1992 ; American Psychiatric Association, 1994 ; Perry, 2014 ; Di Giuseppe and Perry ) is a comprehensive description of both more adaptive (i.e., mature defenses, overlapping in function with coping strategies) and less adaptive (i.e., immature and neurotic defenses) way of automatically responding.…”
mentioning
confidence: 99%
See 1 more Smart Citation